Production of polyethylene composites reinforced with sisal and jute fibres through compression molding. (2022) - Senniangiri, N.; Arunkumar, N.; Dhanabal, A.; Kamalakannan, K.; Thrisul, J.
Abstract: Jute and flax are two of the most appealing fibres for reinforcing polymeric matrices. In response to worldwide environmental needs, the use of these fibres is growing, particularly when combined with thermoforming polymers, to broaden their applications to substitute synthetic fibres and thermosetting plastics. Vegetable fibres low adherence to polymeric matrices is one of their most important drawbacks, which is generally solved by chemical treatments on the fibres or the use of coupling agents inside the matrix. Utilizing woven textiles with a large mesh spacing to enable mechanical anchoring between fibres and matrix, this work studies the manufacture of polyethene (PE) biocomposite laminates reinforced by jute and sisal fibres without extra process steps using the compression moulding method. Two distinct forming procedures were utilised to study how the yarn impregnation was impacted by them. The time it took to reach maximum compression pressure and the time it took to stay at that pressure were different. To enlarge the applications of the composites under consideration, heat deflection temperature, tensile, bending, and Izod tests were completed.